Overview Distress Family to Increase the Quality of Life Communication Disorder in Stroke Patients with Diabetes Mellitus Complication - Febryanto, Dwi; Setyaningrum, Niken; Handayani, Kristiana Prasetya (Indonesian Journal of Global Health Research, 2024)
Communication disorders due to stroke with DM complications negatively impact to self-image, social and emotional well-being and quality of life. On the other hand, not all communication disruptions are reported to have negative impacts. We are interested in examining the picture of family distress in improving the quality of life of sufferers of stroke communication disorders complicated by DM. Objective: This research is important to see whether communication is fully related to the quality of life of stroke sufferers complicated by DM and has an impact on family stress. Method: This research uses a descriptive study design. The sampling technique used was purposive sampling with the plan to involve 30 stroke respondents with DM complications. Quantitative data analysis in the form of univariate and bivariate data. Fisher test is used to see the relationship between variables. Results: The majority of stroke patients with DM complications are women at 63.3%, with a maximum age of 76 years and a minimum age of 40 years. The maximum LAST score result is 15 and the minimum is 3. The highest family stress level result is in the normal category at 70% and the highest quality of life is in the good category at 43.3%. The results of statistical tests on the relationship between family stress levels and the quality of life of sufferers stroke communication disorders with DM complications found that P value = 0.000 < 0.05 Conclusions: Our findings confirm that there are relationship between the level of family stress and the quality of life of sufferers of stroke communication disorders complicated by DM. This is the first time that the research is highlight that family has an important impact on the quality of life stroke sufferers complicated by DM. Improving the quality of life of stroke sufferers complicated by DM by increasing self-care and caring for the family is very important.